Management of localized and advanced prostate cancer in Canada: A lifetime cost and quality‐adjusted life‐year analysis. Issue 7 (1st February 2016) - Sanyal, Chiranjeev; Aprikian, Armen G.; Cury, Fabio L.; Chevalier, Simone; Dragomir, Alice
Abstract : BACKGROUND: To the authors' knowledge, the literature to date lacks studies examining lifetime costs and quality‐adjusted life‐years (QALYs) of prostate cancer (PCa) management strategies that integrate localized and advanced disease. The objective of the current study was to assess lifetime costs and QALYs associated with contemporary PCa management strategies across risk groups by integrating localized and advanced disease. METHODS: The authors' validated Markov chain Monte Carlo model was used to predict lifetime direct costs and QALYs. The health states modeled were active surveillance, initial treatments (radical prostatectomy or radiotherapy), PCa recurrence, PCa recurrence free, metastatic castration‐resistant prostate cancer, and death (cause specific/other causes). Data regarding treatment distribution, state transition probabilities, adverse effects of management options, costs, utilities, and disutilities were derived from the published literature. RESULTS: The total cost per patient for the overall cohort increased from 18, 503 at 5 years to 28, 032 and 39, 143, respectively, at 10 years and 15 years. Furthermore, the results indicated the influence of risk group on total cost, with the high‐risk group accruing the maximum per patient cost followed by the intermediate‐risk and low‐risk groups. Active surveillance was found to confer the most QALYs (12.5 years) and was the least costly strategy (18, 452) for individuals at low risk. For all risk groups, radical prostatectomy was less costly and conferred modestly more QALYs compared with intensity‐modulated radiotherapy modalities. CONCLUSIONS: Public health care systems in Canada and elsewhere are operating under budget constraints to allocate finite resources. The findings of the current study might inform discussions concerning budget planning to provide health care services. Cancer 2016;122:1085–1096. © 2016 American Cancer Society Abstract : In the current study, lifetime costs and quality‐adjusted life‐years appear to be influenced by the level of risk at the time of diagnosis and the initial management option. The value of contemporary management strategies is highlighted by comparative costs and quality‐adjusted life‐years.